(13s+7)(6s-18)=0

Simple and best practice solution for (13s+7)(6s-18)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13s+7)(6s-18)=0 equation:


Simplifying
(13s + 7)(6s + -18) = 0

Reorder the terms:
(7 + 13s)(6s + -18) = 0

Reorder the terms:
(7 + 13s)(-18 + 6s) = 0

Multiply (7 + 13s) * (-18 + 6s)
(7(-18 + 6s) + 13s * (-18 + 6s)) = 0
((-18 * 7 + 6s * 7) + 13s * (-18 + 6s)) = 0
((-126 + 42s) + 13s * (-18 + 6s)) = 0
(-126 + 42s + (-18 * 13s + 6s * 13s)) = 0
(-126 + 42s + (-234s + 78s2)) = 0

Combine like terms: 42s + -234s = -192s
(-126 + -192s + 78s2) = 0

Solving
-126 + -192s + 78s2 = 0

Solving for variable 's'.

Factor out the Greatest Common Factor (GCF), '6'.
6(-21 + -32s + 13s2) = 0

Factor a trinomial.
6((-7 + -13s)(3 + -1s)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-7 + -13s)' equal to zero and attempt to solve: Simplifying -7 + -13s = 0 Solving -7 + -13s = 0 Move all terms containing s to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -13s = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -13s = 0 + 7 -13s = 0 + 7 Combine like terms: 0 + 7 = 7 -13s = 7 Divide each side by '-13'. s = -0.5384615385 Simplifying s = -0.5384615385

Subproblem 2

Set the factor '(3 + -1s)' equal to zero and attempt to solve: Simplifying 3 + -1s = 0 Solving 3 + -1s = 0 Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1s = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1s = 0 + -3 -1s = 0 + -3 Combine like terms: 0 + -3 = -3 -1s = -3 Divide each side by '-1'. s = 3 Simplifying s = 3

Solution

s = {-0.5384615385, 3}

See similar equations:

| 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 | | 0.66x+1=0.50 | | ln(5x+1)=ln(x+11) | | 9x=-11.7 | | 65x-6x=21x+23 | | 6x+6=6(x-5) | | 17h-13h-4h+2h=14 | | 7x-15-10x=15 | | 8x-5=32x-13 | | 11k-9+2k-3= | | 2b+8=2 | | X-8/3=1-x8 |

Equations solver categories